A Management System for Poultry Farm Using LoRa Communication Technology - Siraphop Tooprakai; Ratchapol Krueaprasit; Ratthadramanu Penchalee; Weerapat Tulathon (My University, 2022)
This paper presents A Management System for Poultry Farm Using LoRa Communication Technology. It has the advantage of receiving - transmitting long-distance data and saving energy. It is applied with a sensor node such as temperature and humidity, to collect data in the closed system poultry farm which is 25 meters in width and 100 meters in length. The sensors send data via LoRa technology to the gateway and update data to a database. To collect the data and display, it through a web application in a dashboard. The mobile applications were used to control devices such as fans and pumps to meet optimal conditions for raising broilers.
Keywords: IoT Networks and Protocols